Childhood pneumonia: read the smear and clinch the diagnosis - K., Nandhini; S., Kaveri; S., Elayaraja; P., Umapathy; Ravichandran, Latha (International Journal of Contemporary Pediatrics, 2019)
Childhood pneumonia has a myriad of disease causing organisms. Identifying the etiology often helps us predict the natural course of the illness. We would like to share an interesting child with pneumonia by the hematological manifestation of the disease. Case report of this study is a 8 year old boy who presented with high grade fever for eleven days associated with cough. History of skin rashes which worsened following therapy with penicillin. On Examination child had maculopapular rashes predominantly over the trunk with decreased air entry in the left hemithorax. Chest x-ray done showed left lower lobe consolidation hence treated with cephalosporins and macrolide. Counts revealed falling trend in haemoglobin with high MCV count. Peripheral smear done showed agglutinated RBC’S and occasional nucleated RBC’s. Direct Coombs test was positive. With these haematological manifestations child was diagnosed to have Mycoplasma pneumonia which was proven by positive antibodies against Mycoplasma. Child recovered completely and haematological manifestations became passive after four weeks. Cold agglutinin disease is poorly understood affecting 15% of patients with Autoimmune hemolytic anemia. Respiratory tract involvement and extrapulmonary complications manifest in 3-10% and 25% respectively. Antibodies (IgM) against the I antigen on human erythrocyte membranes appear during the course of M. pneumoniae infection and produce a cold agglutinin response. AIHA typically occurs during 2-3rd week after febrile illness with sudden onset of hemolysis which is self-remitting within 4-6 weeks. The conclusion of this study is extra-pulmonary manifestations in a child with pneumonia help in diagnosing the etiology. This in turn helps us like provide rationale management and Predict the natural course of the illness.